D- and z- values of Escherichia coli O157 H7, Salmonella enterica, and Listeria monocytogenes in Heated Orange Juice. - Pagal, Gladess A.; Gabriel, Alonzo A.
This study was conducted to determine the decimal reduction times (D) and the thermal resistance parameter (z) values of relevant foodborne pathogens linked with fruit juice consumption ? namely Escherichia coli O157:H7, Salmonella enterica, and Listeria monocytogenes. Cocktails of different strains of the same bacterial species were prepared and thereafter subjected to thermal inactivation studies at 50, 53, 55, 57, and 60 °C heating temperatures in orange juice. Survivor populations were determined by surface-plating onto a non-selective medium, after which the inactivation behavior and kinetic parameters were determined. Results showed that for all tested organisms, the D-values significantly (P < 0.05) decreased with increasing heating temperature. In all heating temperatures, E. coli O157:H7 exhibited the significantly greatest heat resistance, with D-values ranging from 324.60 s to 95.12 s. At 50 °C, L. monocytogenes (D-values 152.32 s to 11.84 s) was significantly more resistant than S. enterica (D-values 106.55 s to 19.29 s). At higher heating temperatures, the D-values of S. enterica and L. monocytogenes were not significantly different (P > 0.05). The calculated z-values significantly varied across the test organisms, which ranged from 9.40 °C (L. monocytogenes) to 18.78 °C (E. coli O157:H7). These results may be used in the establishment of new, and validation of existing, thermal process schedules to ensure safety against the test pathogens.